STRONGYLOIDES CRUZI (RHABDITIDA: STRONGYLOIDIDAE) IN OPHIODES STRIATUS (SQUAMATA: ANGUIDAE) FROM BRAZIL: NEW HOST AND LOCALITY RECORDS WITH TAXONOMIC COMMENTS ON STRONGYLOIDES OF LIZARDS - Tenório Mati, Vitor Luís (2013)
Strongyloides cruzi Rodrigues, 1968 was found in Ophiodes striatus (Spix, 1825) from Itabirito, state of Minas Gerais, Brazil. The morphology of the nematodes obtained was briefly described and compared with previous reports of Strongyloides spp. from lizards. Taxonomic comments about these parasites are presented and a species of Strongyloides, a genus whose members have rarely been reported in lizards, is for the first time observed in an anguid reptile.